2004
DOI: 10.1038/sj.eye.6700688
|View full text |Cite
|
Sign up to set email alerts
|

Can a public health package on glaucoma reach its target population?

Abstract: Purpose A pilot study to assess how successful a newspaper advertisement and a radio interview about glaucoma are at reaching their target population. Methods The health intervention comprised two components: an interview on local radio and an advertisement in the local paper. Our target population were residents aged 45 years and above in either Southall (West London) or the Isle of Wight (IOW). A questionnaire was developed to be carried out pre-and postintervention. The data from both locations pre and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Baker et al 24 reported that while social marketing media strategies raise awareness about glaucoma, they do not influence health seeking behaviour. They advocate the addition of interpersonal interaction and community development to produce a change in behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al 24 reported that while social marketing media strategies raise awareness about glaucoma, they do not influence health seeking behaviour. They advocate the addition of interpersonal interaction and community development to produce a change in behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study has shown that knowledge of glaucoma in the Indian population in Southall Ealing was low 12. Our research group has gained considerable background information on positive predictive values of glaucoma referrals and optometric practice within the area 13.…”
Section: Methodsmentioning
confidence: 99%
“…Conclusion: Glaucoma specialists are familiar with the treatment patterns of their patients. The knowledge of glaucoma specialists of their patients' subjective attitudes to glaucoma-related issues deserves further Introduction Public awareness of glaucoma and patients' compliance in glaucoma management have been investigated in several recent studies [1,2,4,7,8,10,12,14,16]. Interestingly, no data are available about glaucoma doctors' knowledge and insight into the patients' circumstances or opinions [5,6,9] of their disease.…”
Section: What Do Glaucoma Specialists Know About Their Patients?mentioning
confidence: 98%